CybergeoNet – Traductions scientifiques - Christine Kosmopoulos; Natacha Aveline; Colette Cauvin-Reymond; Bernard Elissalde; Maria Gravari-Barbas; Margaux Hardy; Nathalie Lemarchand; Francisco Maturana; Denise Pumain; Benjamin Wayens; Gloria Zamorano (Cybergeo, 2022)
Created in 1996, Cybergeo, European Journal of Geography is native digital journal which was conceived from the start for publication in all European languages. In order to better promote its authors’ articles internationally, it is undertaking actions to improve and translate its metadata into English, Spanish and Chinese. CybergeoNet is a laureate of the AAP "Scientific Translations" launched in 2019 by the Ministry of Higher Education, Research and Innovation (MESRI) in France. It has developed an efficient, and quality, collaborative translation method that is transferable to other scientific journals published and managed by research laboratories. The aim is to ensure that authors and editorial teams become more competent in translation. A guide of good practices is proposed to the community. The impact of linguistic improvements made to the journal’s metadata is also measured with the consultation statistics provided by the OpenEdition platform. All documents are freely available online.